Penanaman Pendidikan Karakter Melalui Legenda Ajisaka sebagai Alat Kontrol Sosial di Masyarakat - Ella Fazira; Delfi Kholifatun Nisa`i; Vivi Julviani; Luthfa Nugraheni (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing involvement of childern in criminal activitties highlights the urgent need for character education to develop future generations with strong moral integrity. This study explores the use of the Legend of Ajisaka as a medium for instilling character values and as a tool for social control. Using a qualitative library research method, the study analyzes narrative elements, symbols, and characters in the Serat Manikmaya version of the Ajisaka legend. The analysis reveals seven of the eighteen character values outlined by the Indonesian Ministry of Education and Culture, including religiousness, honesty, hard work, creativity, patriotism, social care, and responsibility. Among these, religiousness and creativity appear most prominently, depicting Ajisaka as both a spiritual and innovative figure. The findings suggest that the legend can effectively convey moral messages, strengthen cultural identity, and serve as an instructional resource in elementary school character education. The study emphasizes the dual function of folklore in not only shaping individual character but also reinforcing social norms within communities.